Evolution of Shariah Governance Practices in Shariah Risk Management Function from The Institutional Theory Perspective - Salleh, Salina; Mohd Alwi, Norhayati; Mohd Ariffin, Noraini (International Journal of Economics, Management and Accounting, 2025)
This research aims at elucidating the evolution of Shariah governance practices in a Malaysian Islamic bank by examining the progression toward institutionalization through the lens of Institutional Theory. A qualitative research approach was employed, drawing on existing literature, case studies, and interviews with experts in Shariah risk management function. An explanatory case study was done to deeply understand the institutionalization of Shariah governance practices due to the evolution of framework and policy from Shariah Governance Framework (SGF) 2010 to the latest Shariah Governance Policy Document (SGPD) 2019. This research delves into the development of Shariah governance from SGF 2010 to SGPD 2019, with a particular focus on the institutionalization of the Shariah risk management function in an Islamic bank. Analyzing the outcomes through the framework outlined by Burns and Scapens in 2000 within the context of Institutional Theory, the research highlights how this evolution has fortified Shariah governance practices over time, indicating a shift toward greater alignment in an Islamic bank with Shariah governance. However, a notable limitation persists in ensuring the competency and expertise of Shariah officers, particularly in their adaptation to institutional and actionable realms in routinizing the rules. This research paper enriches understanding of institutionalization, emphasizing its pivotal role in fostering trust, providing support, and enabling optimal performance among Shariah officers. It highlights the importance of continuous learning and skill development for Shariah officers, asserting that competency and expertise can evolve progressively. Consequently, the Shariah governance practices in Islamic banks have exhibited increased robustness, effectively mitigated Shariah non-compliance risks, and demonstrated heightened adherence to Shariah governance and compliance.